Pengaruh Sistem Perpajakan, Keadilan Pajak, Love Of Money, Diskriminasi Pajak, Teknologi dan Informasi Perpajakan terhadap Persepsi Wajib Pajak Orang Pribadi Mengenai Etika Penggelapan Pajak - Putri Kharisma Mochtar; Dwi Yana Amalia Sari Fala; Irfan Zam Zam (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The objectives of this study are: To analyze the effect of the taxation system, tax justice, love of money, tax discrimination, technology and tax information on the perception of individual taxpayers regarding the ethics of embezzlement. The population used in this study were all individual taxpayers registered at KPP Pratama Ternate. Sample withdrawal based on simple random sampling. Based on Slovin's calculation, the sample size was 362 respondents. The type of data used in this study is quantitative data and data analysis using the SPSS 25 application. The method used is Multiple Linear Regression Analysis. The results of this study indicate that the Taxation System has no effect on the perception of individual taxpayers regarding the ethics of tax evasion, while Tax Justice, Love Of Money, Tax Discrimination, Technology and Tax Information affect the perception of individual taxpayers regarding the ethics of tax evasion.